Effect of hydroxyapatite content and particle size on the mechanical behaviors and osteogenesis in vitro of polyetheretherketone–hydroxyapatite composite. Issue 12 (21st September 2021) - Li, Shuai; Wang, Tianyu; Hu, Jiqiang; Wang, Bing; Li, Yingze; Wang, Lianchao; Li, Gao; Zhang, Jialin; Zhou, Zhengong
Abstract: Poly‐ether‐ether‐ketone (PEEK) possesses excellent biocompatibility and similar elastic modulus as bones but suffers from poor osseointegration; usually, the addition of hydroxyapatite (HA) is considered as an effective way to improve the osseointegration of PEEK implant interface. To investigate the effect of HA content and particle size on the mechanical behaviors and osteogenesis in vitro of PEEK‐HA composites, the PEEK‐HA specimens with variable HA content and particle size have been fabricated by powder mixing‐heat press method and characterized by mechanical and biological tests. The results showed that the tensile/bending strength and elongation at break of PEEK‐HA are significantly impaired as the increasing HA amount, but the modulus improves. The compressive strength and modulus are improved as the increasing amount of HA. The PEEK‐HA with smaller HA particle size possesses higher‐performance tensile/bending and lower‐performance compressive properties. In osteogenesis tests in vitro, the results reveal that the cells amount attached on the substrate rises and the cells flatten more evenly with numerous cytoplasmic processes on greater area with the increasing HA content and decreasing particle size. The PEEK‐HA group that HA content is 20 wt% and particle size is 20 nm exhibits optimal‐performance osteogenesis in vitro, while maintaining sufficient mechanical properties. Abstract :